PTPN18 Stimulates the Development of Ovarian Cancer by Activating the PI3K/AKT Signaling. (11th March 2022) - Mao, Nan; Li, Hu; Yang, Hui; Su, Jianfen; Liang, Zhimin; He, Guansheng
Abstract : Objective . To illustrate the functions of protein tyrosine phosphatase nonreceptor type 18 (PTPN18) in the progression of ovarian cancer and the potential molecular mechanism. Methods . Differential PTPN18 expression in ovarian cancer samples was determined. Following PTPN18 knockdown, changes in proliferation and migration in ovarian cancer cells were detected. Nude mice with ovarian cancer were used to uncover the effects of PTPN18 on ovarian cancer growth in vivo. Results . PTPN18 was significantly upregulated in ovarian cancer samples and linked to pathological staging and metastasis rate. PTPN18 displayed prognostic and diagnostic potentials in ovarian cancer. Knockdown of PTPN18 and treatment of the PI3K inhibitor could inhibit proliferative and migratory abilities in ovarian cancer cells. Moreover, PTPN18 was capable of inactivating PI3K/AKT signaling. In vivo knockdown of PTPN18 suppressed ovarian cancer growth in nude mice. Conclusions . PTPN18 is upregulated in ovarian cancer, which stimulates the malignant development by activating PI3K/AKT signaling. The PTPN18 level is also associated with pathological staging and metastasis in ovarian cancer patients, which may be utilized as a hallmark predicting the malignant level.